Odpowiedzi

2009-12-03T21:05:20+01:00
A) 3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=34

m=2
n=9-3*2=3


b) 4a-2=b
3a+7b=1,5

4a=b+2
3a+7b=1,5

a=b/2+0,5
3(b/2+0,5)+7b=1,5

a=b/2+0,5
3b/2+1,5=1,5

a=b/2+0,5
3b=0

a=b/2+0,5
b=0

b=0
a=0,5


c) 5x=4-2y
4x+y=3

y=3-4x
5x+2(3-4x)=-4

y=3-4x
5x+6-8x=-4

y=3-4x
-3x=-10

y=3-4x
x=0,3

x=0,3
y=1,8


d) 6x-3y=9
x+5y=-9,5

x=-9,5-5y
6(-9,5-5y)-3y=9

x=-9,5-5y
-57-30y-3y=9

x=-9,5-5y
-33y=66

y=-2
x=0,5
2 4 2
2009-12-03T21:05:50+01:00
A)
3m+n=9
2m-5n=-11

n=9-3m

2m-5(9-3m)=-11
2m-45+15m=-11
17m=34
m=2
n=9-3*2=3


b)
4a-2=b
3a+7b=1,5

3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=15,5
a=1/2
b=4*(1/2)-2=0


c)
5x=4-2y
4x+y=3

y=3-4x

5x=4-2(3-4x)
5x=4-6+8x
-3x=-2
x=2/3
y=3-4*(2/3)=1/3

d)
6x-3y=9
x+5y=-9,5

2x-y=3
y=2x-3

x+5(2x-3)=-9,5
x+10x-15=-9,5
11x=5,5
x=1/2
y=2*(1/2)-3=-2
1 5 1